Last Glacial Maximum Human Occupation of the Transbaikal, Siberia. (October 2015) - Buvit, Ian; Terry, Karisa; Izuho, Masami; Konstantinov, Mikhail V.; Konstantinov, Aleksander V.
Abstract : We analyze the late Pleistocene radiocarbon chronology of the Transbaikal region of Siberia and conclude that humans inhabited the area during parts of the Last Glacial Maximum, but completely abandoned it between 24, 800 and 22, 800 cal yr BP. Moreover, the distinct contrast between non-microblade producing sites and those with microblades on either side of the radiocarbon gap suggests that the new technology arrived with recolonization.